Assessing psychometric of the perceived stress scale and identifying stress-associated factors in a sample of Ukrainian female refugees in the Czech Republic - Iryna Mazhak; Kateryna Maltseva; Danylo Sudyn (Elsevier, 2024)
Introduction: The full-scale Russian war has caused refugees to experience many stressful events, which may have a long-term adverse impact on their physical and mental health. Understanding the factors associated with increasing/decreasing stress is essential for the psychosocial support services for refugees. The Perceived Stress Scale (PSS) is a popular tool for assessing life stress perception through self-reporting. The purposes of the study were: 1) to examine the psychometric qualities of the Ukrainian versions of the PSS-14 and PSS-10; 2) to determine the level of perceived stress; 3) to reveal factors associated with perceived stress in the sample of Ukrainian female refugees in the Czech Republic (N = 919). Methods: Perceived stress was measured by the Ukrainian versions of the Perceived Stress Scale (PSS-14 and PSS-10) which were validated by applying exploratory and confirmatory factor analysis. Linear regressions were run to understand associations between self-reported physical health conditions, the barriers to adaptation in the host country, the determinants of social health and perceived stress. Results: Both PSS-14 and PSS-10 scales had a high level of internal consistency. Two factors (involving positive and negative items) were extracted based on exploratory factor analysis. The external consistency was confirmed by analysing correlations of the PSS-14/PSS-10 and coping strategies as well as self-reported physical and mental health. Ukrainian female refugees in the Czech Republic experienced moderate to high levels of perceived stress. The study found that on the one hand, a decrease in self-reported physical and mental health statuses, worsening health due to the war, low housing quality, financial disadvantages, experience of cultural differences issues and discrimination, healthcare access inequalities, lack of Czech language skills, failure to integrate into social activities within Ukrainian community, lack of social support, and applying an avoidant coping strategy are factors associated with forced migration that could increase perceived stress in the sample of Ukrainian female refugees. On the contrary, the level of perceived stress of participants could decrease with increasing social support, including such factors as regular communication with relatives and friends who are staying in Ukraine, and having good relations with loved ones, friends, and locals. Conclusions: The Ukrainian version of PSS-10 has good psychometric properties and can be relied upon to measure perceived stress. The study revealed factors associated with the perceived stress in the sample of Ukrainian female refugees in the Czech Republic and emphasised the necessity of psychosocial support services and developing interventions to help cope with stress among Ukrainian female refugees in the host country.